Glacier Surface Speed Variations on the Kenai Peninsula, Alaska, 2014–2019. Issue 3 (22nd March 2022) - Yang, Ruitang; Hock, Regine; Kang, Shichang; Guo, Wanqin; Shangguan, Donghui; Jiang, Zongli; Zhang, Qibing
Abstract: To characterize the spatiotemporal variations of glacier surface speed on the Kenai Peninsula, Alaska (∼3, 900 km 2 ), we derived 92 surface speed fields between October 2014 and December 2019 using intensity offset tracking on Sentinel‐1 data. On average, speeds are 50% greater in spring (March‐May) than the annual mean (69 m a −1 ) while winter speeds are close to the annual mean. While marine‐terminating glaciers have their maximum speed near the terminus, both land‐ and lake‐terminating glaciers flow fastest around the median glacier elevation. On average, the lake‐terminating and tidewater glaciers flow 1.7 and 2.3 times faster than the land‐terminating glaciers, respectively. Monthly variations over the 5‐year period are strikingly synchronous regardless of terminus type suggesting that regional‐scale meteorological drivers govern the temporal variability. Mean annual speeds fluctuate roughly ±10% of the period mean without an apparent trend. At lake‐terminating Bear Glacier, a short‐term tripling in ice speed in fall 2019 over the area below an ice‐dammed lake coincides with an observed glacier lake outburst flood (GLOF). An earlier GLOF caused a persistent breach of the beach barrier between the proglacial lake and ocean which likely led to overall speed‐up of the lower glacier part throughout 2019. A significant speedup was also observed at the lower part of the lake‐terminating Ellsworth Glacier and attributed to rapid glacier retreat and lake expansion, probably further amplified by the terminus area becoming buoyant and a large tabular iceberg breaking off. Our results highlight the impact of GLOFs and proglacial characteristics in spatial and temporal glacier speed variations. Plain Language Summary: Glaciers constantly move but the speed varies with time and space. We use satellite data to calculate the surface ice speed variations of all glaciers on the Kenai Peninsula, Alaska (∼3, 900 km 2 ), between October 2014 and December 2019. On average, the glacier speed is 50% higher in spring than the annual average. Overall, the lake‐terminating glaciers flow 70% faster, and marine‐terminating glaciers more than 100% faster than the land‐terminating glaciers. Over the 5‐year period, all glaciers regardless of terminus type tended to speed up or slow down simultaneously, probably driven by large‐scale variations in weather governing the water supply to the drainage system. The lower part of Bear Glacier tripled in speed in fall 2019 when an ice‐dammed lake suddenly drained through the glacier. Another glacier outburst flood in 2018 led to a breach of the beach barrier between the large lake at the glacier terminus and the ocean which might have caused the considerable speedup of the lower glacier part throughout 2019. Key Points: Lake‐terminating glaciers flow 1.7 times and tidewater glaciers 2.3 times faster than the land‐terminating glaciers Monthly ice speed variations are largely synchronous across the Peninsula irrespective of terminus type A glacier outburst flood at Bear Glacier caused both a short‐term and a longer‐term speed‐up of the glacier's lower part